THU0195 Incidence of Infliximab (IFX) Infusion Reactions with and Without Premedication. (23rd January 2014) - Bartoli, F.; Fiori, G.; Galluccio, F.; Nacci, F.; Salvadorini, G.; Matucci Cerinic, M.
Abstract : Background: Some patients may experience adverse drug reactions (ADR) during infusion with IFX and this could be due to immunogenicity. Objectives: To evaluate the incidence of infusion reactions in rheumatoid arthritis (RA) patients, seronegative spondiloarthritis (SpA) and psoriatic arthritis (PsA) receiving IFX with and without premedication Methods: The charts of 75 patients treated with infliximab from 2000 to 2012 were reviewed. From 2001 to 2006 patients did not receive any medication before IFX, while from 2007 to 2011 patients received premedication with paracetamole (500 mg) and iv with esomeprazole 40 mg iv, hydrocortisone 5 mg/Kg, clorfenamine 10 mg. From 2011 on, premedication was modified as follows: paracetamole 500 mg, Hydroxizine 25 mg and iv ranitidine 50 mg, 6-methilprednisolone 100 mg. Results: From 2001 to 2006 when premedication was not yet used, 21/75 (28%) patients had infusional reactions to IFX. From 2007 to 2011 9/67 (13.4%) patients had infusional reactions after introduction of corticosteroids and antihistamines premedication. Moreover, 1/57 patient (1.7%) had infusional reaction in the last two years using premedication with 6-methilprednisolone iv and ranitidine iv. The number of infusion reactions was significantly lower using premedication with corticosteroids and antihistamines (p <0.05). The incidence of infusional reactions was significantly reduced (p <0.05) with paracetamole, hydroxyzine and 6-metilprednisolone 100 mg and ranitidine iv before IFX treatment. No one anaphylactic reactions was observed. Conclusions: In our experience, the combination of drugs in a premedication protocol with paracetamole, hydroxyzine, 6-methilprednisolone and ranitidine iv reduced significantly the number and severity of infusional reactions to IFX. References: Sany J, Kaiser MJ, Jorgensen C, Trape G. Study of the tolerance of infliximab infusions with or without betamethasone premedication in patients with active rheumatoid arthritis. Ann Rheum Dis. 2005 Nov;64(11):1647-9. Okuyama A, Nagasawa H, Suzuki K, Kameda H, Kondo H, Amano K, Takeuchi. Fcγ receptor IIIb polymorphism and use of glucocorticoids at baseline are associated with infusionreactions to infliximab in patients with rheumatoid arthritis. Ann Rheum Dis. 2011 Feb;70(2):299-304. Epub 2010 Oct 27. Lequerré T, Vittecoq O, Klemmer N, Goëb V, Pouplin S, Menard JF, Daragon A, Mejjad O, Le Loët X. Management of infusion reactions to infliximab in patients with rheumatoid arthritis or spondyloarthritis: experience from an immunotherapy unit of rheumatology. J Rheumatol. 2006 Jul;33(7):1307-14. Epub 2006 Jun Disclosure of Interest: None Declared